Effect of the Gap Size between the Cathode and the Wehnelt Cylinder Bore on the Emittance of the Thermionic Electron Gun - Mohammed, Najia Abdullah; Al-Abdullah, Abdullah Idrees (Iraqi Journal of Science, 2022)
This paper includes simulating an electron gun design to investigate the effect of the distance between the cathode and the Wehnelt cylinder bore on the quality of the ion beam emittance and to obtain the best distance of that geometrical factor. A study of a group of designs was conducted to find this distance. The SIMION8.0 program has been used to calculate the trajectories of the electrons with initial kinetic energy of (0.1 eV) and electron current of (1×10-12 A). The investigation also includes comparisons between the equipotential line trajectories for each design as well as the field distribution and the electron trajectories. The best emittance distance was concluded to be (3 mm).